Metalurgie a vlastnosti masivních ocelových odlitků - Kubík, Jiří (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2013)
Práce se zabývá stanovením chemického složení a morfologie vměstků u experimentálního odlitku v provozních podmínkách slévárny ŽĎAS a.s. při dodržení optimálního obsahu vhodných dezoxidovadel v závislosti na podmínkách tuhnutí. Úvodní část práce je věnována teoretickému rozboru možných vad v odlitcích. Dále je popsán experimentální odlitek, místa odběru vzorků a jejich značení. Následně je vyhodnocena morfologie, mikroanalýza vměstků a vliv vměstků na mechanické vlastnosti a vznik vad v odlitku. Závěr obsahuje shrnutí výsledků a návrh dalšího směru ve výrobě masivních ocelových odlitků.

The work deals with the determination of the chemical composition and morphology of inclusions in experimental casting foundry in operating conditions as ŽĎAS in compliance with the optimum content appropriate deoxidation depending on the conditions of solidification. The introductory part is devoted to theoretical analysis of possible defects in castings. We also describe the experimental casting, sampling sites and their markings. Subsequently evaluated morphology microanalysis inclusions and the effect of inclusions on the mechanical properties and the formation of defects in the casting. The conclusion summarizes the results and proposal for further direction in the production of heavy steel castings.
Metallurgy and properties of heavy steel castings
Keywords: Vměstky; dezoxidace oceli; morfologie; vady; masivní; odlitek; Inclusions; deoxidation of steel; morphology; defects; massive; casting